Embedding digital agriculture into sustainable Australian food systems: pathways and pitfalls to value creation. Issue 3 (4th May 2022) - Cook, Simon; Jackson, Elizabeth L.; Fisher, Myles J.; Baker, Derek; Diepeveen, Dean
ABSTRACT: Digital agriculture is exciting attention because of an expectation that food systems will be disrupted by new digital technologies through improvements in precision, efficiency, volume, speed of process or identity of product. This is against the background of the drive for sustainability in food systems. A diversity of technology applications is unilaterally emerging in all food chains with benefits realized through human acceptance and adoption in business processes. This paper focuses on Australia but the lessons apply to digital agriculture globally. We propose that sustainable food systems frameworks identify the relation of individual changes to broader systemic change, to relate individual changes to one another and to understand how multiple changes within a system can trigger major shifts in entire agri-food chains. With this rapidly-changing landscape in mind, we argue that food system frameworks cover five domains: production, market, capitals, governance and data technologies. We analyse experience from agricultural systems, compare it to digitization in non-agricultural systems and conclude that change will be both disruptive and cumulative. We consider the role of systems governance to be under-reported. Governance will prove critical in areas of IP legislation, policy harmonization and targeted investment.